(untitled) (Journal of Universal Science Research, 2025)
This is quite a narrow research objective that is focused on the benefits and challenges regarding the Computer-Aided Assessment, and how it impacts the students’ knowledge at the University. The field of education is constantly changing, and it has come to a stage where technology has been incorporated into teaching. One of the most important changes is the development of the Computer Aided Assessment (CAA), which uses technology to assess the students ‘learning. This article tries to study the effectiveness of CAA in language teaching and analyze its effects on students learning, educational practices, as well as the general participation of students in the educational process. Most of the foreign language classes taught at the Andijan branch of Kokand University in Uzbekistan were recorded for study purposes. A number of barriers concerning the use of modern technology in these lessons were discovered. Among such challenges were technical issues, insufficient computers or other devices, and the students’ associated lack of knowledge. Some teachers who participated in the classroom technology integration were interviewed for the purpose of understanding the design challenges. The investigators made with the impression that the teachers, despite challenges in implementing technology into teaching in these classes, had an overall positive attitude toward technology integration.